A genetic analysis of various functions of the TyrR protein of Escherichia coli. - Yang, J (1993)
The TyrR protein is involved in both repression and activation of the genes of the TyrR regulon. Correction of an error in a previously published sequence has revealed a Cro-like helix-turn-helix DNA-binding domain near the carboxyl terminus. Site-directed mutagenesis in this region has generated a number of mutants that can no longer repress or activate. Deletions of amino acid residues 5 to 42 produced a protein that could repress but not activate. The central domain of TyrR contains an ATP-binding site and is homologous with the NtrC family of activator proteins. A mutation to site A of the ATP-binding site and other mutations in this region affect tyrosine-mediated repression but do not prevent activation or phenylalanine-mediated repression of aroG.